2019
DOI: 10.1002/adfm.201806778
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Electrochemical Actuation of MnO2/Ni Bilayer Film Derived by Redox Pseudocapacitive Process

Abstract: Pseudocapacitance-induced electrochemical actuators (EC-actuators) have attracted great attention in robots and artificial intelligence technologies.Despite major efforts to design such EC-actuators, a molecular-level understanding of the deformation mechanism is still lacking. Here, a reversible deformation of a freestanding MnO 2 /Ni bilayer film is demonstrated and in situ electrochemical atomic force microscopy, in situ Raman spectroscopy, and density functional theory simulation are used to study the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 57 publications
(125 reference statements)
3
63
0
Order By: Relevance
“…The corresponding samples after electrochemical deposition was named as npg + x MnO 2 ( x is the cycles of MnO 2 deposition). The X-ray diffraction (XRD) pattern revealed that the obtained MnO 2 material in an electrochemical deposition manner was -MnO 2 (see Figure 1 a), consistent with the previous reports [ 37 ]. The crystal structure did not change after applying the electrochemical potentials.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…The corresponding samples after electrochemical deposition was named as npg + x MnO 2 ( x is the cycles of MnO 2 deposition). The X-ray diffraction (XRD) pattern revealed that the obtained MnO 2 material in an electrochemical deposition manner was -MnO 2 (see Figure 1 a), consistent with the previous reports [ 37 ]. The crystal structure did not change after applying the electrochemical potentials.…”
Section: Methodssupporting
confidence: 89%
“…The charge can be stored in the MnO 2 layer by the reversible redox reaction in a neutral electrolyte (Na 2 SO 4 ) during the electrochemical charge and discharge process according to Equation (2) [ 37 ]: …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This principle has been used to synthesize a large variety of functional materials that undergo reversible change in their size, shape, and corresponding physical properties . A pre‐requisite for fabricating such shape changing materials is physical or chemical binding of two (or more) layers of materials with dissimilar stimuli‐induced strains . Fabricating such anisotropic materials requires complex synthetic approaches, such as lithography, which limits the large scale applicability of these adaptive and responsive materials.…”
Section: Methodsmentioning
confidence: 99%